CREATIVE PEDAGOGICAL COMPETENCE AND INNOVATIVE TEACHING METHODS - Feruzabonu Ravshanova (Bright Mind Publishing, 2025)
This article presents a scientific and theoretical overview of the role and significance of creative pedagogical competence and innovative teaching methods in the modern educational process. Today, teachers are expected not only to possess deep subject knowledge but also to think creatively, develop new approaches, and utilize effective methods that can increase student engagement. Accordingly, the article explores the essence of creative competence, its components, ways of development, and the innovative approaches expected from modern educators. Specifically, the article analyzes how methods such as interactive learning, project-based teaching, STEAM technologies, and accelerated learning can make lessons more engaging and effective. The positive impact of innovative teaching methods on students' personal development, creative thinking formation, and knowledge retention is discussed on a scientific basis. Furthermore, practical recommendations are offered on how to develop creative competence in teachers’ pedagogical practice. This article serves as a useful methodological resource for educators, methodologists, and future teachers in organizing modern and effective lessons.
Keywords: Creative competence, innovative teaching methods, pedagogical skills, interactive teaching technologies, STEAM approach, project-based learning, creative thinking, educational innovation, student motivation, new pedagogical technologies.